Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 8 - Radical Functions - 8.3 Multiplying and Dividing Radicals - 8.3 Exercises: 87

Answer

$28+4\sqrt 6+7\sqrt {2x}+3\sqrt {3x}$

Work Step by Step

$\sqrt {3x}+(4+\sqrt {2x})(7+\sqrt 6)$ =$\sqrt {3x}+[4(7+\sqrt 6)+\sqrt {2x}(7+\sqrt 6)]$ =$\sqrt {3x}+(28+4\sqrt 6+7\sqrt {2x}+\sqrt {6\times2x})$ =$\sqrt {3x}+28+4\sqrt 6+7\sqrt {2x}+\sqrt {12x}$ =$\sqrt {3x}+28+4\sqrt 6+7\sqrt {2x}+\sqrt {4\times3x}$ =$\sqrt {3x}+28+4\sqrt 6+7\sqrt {2x}+2\sqrt {3x}$ =$28+4\sqrt 6+7\sqrt {2x}+2\sqrt {3x}+\sqrt {3x}$ =$28+4\sqrt 6+7\sqrt {2x}+3\sqrt {3x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.